MENGUNGKAP BUDAYA KONSUMSI MEDIA BURUH PEREMPUAN LEWAT PERSPEKTIF CULTURAL STUDIES (Studi Etnografi pada Buruh Industri & Rumah Tangga di Malang) - Mariani, Ana (Jurnal Nomosleca, 2016)
Abstract Mass media have become an integral part of modern society and played a significant social and political role. Antonio Gramsci view mass media as an organic intellectual of the capitalists to defend their interests. Media omnipresence left none of society member including female labor from using them to support his/her daily lives. Media use among the usually underpaid female labors and the reason behind their media consumption is the main concern of the research. The ethno-graphic research attempts to describe how and why they do so. What are the social and political advantages they obtained when consuming media to enhance their class- consciousness. After observing six informants and interviewing them on the matters regarding how and why the use media along what media they prefer most, it found that they did so merely for pleasing themselves by just watching the television program without intending to improve skills and knowledge necessary to enhance their required political class-consciousness. Media literacy is urgently required for them to enable them to use media wisely. By so doing, they could acquire the skills to prevent them from bad media effects.DOI :Â https://doi.org/10.26905/nomosleca.v2i1.345